The Zero-Condition: A Simplifying Assumption in QALY Measurement and Multiattribute Utility - Miyamoto, John M.; Wakker, Peter P.; Bleichrodt, Han; Peters, Hans J. M. (Management Science, 1998)
This paper studies the implications of the “zero-condition” for multiattribute utility theory. The zero-condition simplifies the measurement and derivation of the Quality Adjusted Life Year (QALY) measure commonly used in medical decision analysis. For general multiattribute utility theory, no simple condition has heretofore been found to characterize multiplicatively decomposable forms. When the zero-condition is satisfied, however, such a simple condition, “standard gamble invariance,” becomes available.